Construction of the analytical solution of uranium nuclear radioactive series - Mohammed Shqair (Results in Physics)
In this paper, the Uranium nuclear radioactive series, an essential radioactive series in nuclear physics, is fully studied and solved analytically, for the first time, using the homotopy perturbation method (HPM). This work begins by considering single-step radioactive decay and then proceeds to study the successive radioactive decay (parent, daughter, and granddaughter nuclei). The primary focus is the general case of the Uranium nuclear radioactive series, the numerical nuclear physics data for the Uranium nuclear radioactive series, as well as both simplifications are considered.